2022
DOI: 10.1590/1678-9865202235e210199
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of nutritional supplements by teenagers attending gyms supplements and exercise in teenagers

Abstract: Objective: To describe the supplements used by adolescents in gyms in the city of São Paulo and the factors related to their use. Methods: Participants were 1,012 adolescents of both sexes, aged between 13 and 18 years old, all of them regular regulars at gyms in the city of São Paulo. For data collection, a questionnaire was used to identify the main supplements consumed by adolescents. The chi-square test was used to verify possible associations with a significance of p<0.05. Results: The use of supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…Previous studies found that the reason for supplementation among adolescents was due to the parent's advice rather than doctors' instruction or other unspecified reasons (Lee et al, 2013;Sien et al, 2014). In another study by Ceschini et al (2022), 29.3% of adolescents in the municipality of Brazil were found to consume VMS without any professional guidance (self-prescription). Additionally, a vast number of current findings highlighted that no matter whether adults or adolescents, the reason they consumed dietary supplements is to maintain and improve their overall health level, also to prevent diseases (Cebula et al, 2018;Elsahoryi et al, 2023;Perlitz et al, 2019;Shahzad et al, 2022;Sicinska et al, 2022;Yazid et al, 202) as they believed that supplements help achieve their recommended nutrient intake (Hoover et al, 2017).…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies found that the reason for supplementation among adolescents was due to the parent's advice rather than doctors' instruction or other unspecified reasons (Lee et al, 2013;Sien et al, 2014). In another study by Ceschini et al (2022), 29.3% of adolescents in the municipality of Brazil were found to consume VMS without any professional guidance (self-prescription). Additionally, a vast number of current findings highlighted that no matter whether adults or adolescents, the reason they consumed dietary supplements is to maintain and improve their overall health level, also to prevent diseases (Cebula et al, 2018;Elsahoryi et al, 2023;Perlitz et al, 2019;Shahzad et al, 2022;Sicinska et al, 2022;Yazid et al, 202) as they believed that supplements help achieve their recommended nutrient intake (Hoover et al, 2017).…”
Section: Introductionmentioning
confidence: 94%